Knowledge, Attitude, Social Support and Determinants of Exclusive Breastfeeding Among the mothers of Child Below 6 Months: A Cross-Sectional Study of Damak Municipality - Rai, Diwas; Uprety, Pravat (Nepalese Journal of Statistics, 2025)
Introduction: Exclusive breastfeeding during the first six months of life is critical for infant health. Despite the national and international promotions and guidelines, the rate remains subpar. Objective: To estimate the prevalence of exclusive breastfeeding and determine the factors of exclusive breastfeeding in the Damak municipality of Jhapa. Materials and Methods: A cross-sectional study was conducted among 388 mothers using a structured questionnaire. The sampling frame was constructed using vaccine records. Data were analyzed using the concept of descriptive statistics, chi-square, and Mann-Whitney U tests for bivariate analysis and binary logistic regression for multivariate analysis. Model diagnostics included Hosmer-Lemeshow test, Analysis of Deviance, Generalized Variance Inflation Factor, AUC and pseudo-R2. Reasons for early cessation of breastfeeding were asked to non-EBF mothers. Results: The EBF prevalence was 32.99% (95% CI: 28.31%-37.67%). Logistic regression identified initiation of breastfeeding (within an hour) (AOR=3.32, 95% CI: 1.8-6.88, p<0.001), maternal knowledge (AOR=1.95, 95% CI: 1.03-3.73, p=0.04), maternal age 35-44 years (AOR=0.37, 95% CI: 0.15-0.84, p=0.021), job/wage income (AOR=2.18, 95% CI: 1.17-4.06, p=0.014) and infant age 4 months (AOR=0.40, 95% CI: 0.17-0.91, p=0.033) and 5 months (AOR=0.29, 95% CI: 0.12-0.68, p=0.005) as significant predictors. Attitude and morbidity were not statistically significant. Perceived milk insufficiency (72.85%) and perceived infant thirst (28.05%) are major leading causes of early supplementation. Conclusion: EBF in Damak is significantly below the national average. Key determinants include initiation of breastfeeding, knowledge, major income source, mother’s age and infant age in months. While attitude and morbidity were positively related, but it was not statistically significant. Lastly, 76% of the mothers had poor knowledge which highlights the knowledge gaps that affecting exclusive breastfeeding practice.